Bootstrap related tools & skills - Perna, Maria Antonietta (SitePoint, 2018)
Bootstrap stands as one of the most popular, open-source, front-end frameworks on the Web. Since its official release in 2011, it has undergone several changes, and it's now one of the most stable and responsive frameworks available. It's loved by web developers of all levels, as it gives them the capability to build a functional, attractive website design within minutes. A novice developer with just some basic knowledge of HTML and little CSS can easily get started with Bootstrap. In this book, we'll look at some related tools and skills that will help you with Bootstrap development. It contains: 15 Bootstrap Tools and Playgrounds by David Attard An Introduction to Grid Systems in Web Design by Callum Hopkins Bootstrap UI Libraries for Angular, React and Vue.js by Maria Antonietta Perna Bootstrap Grid: Mastering the Most Useful Flexbox Properties by Ahmed Bouchefra Bootstrap Sass Installation and Customization by Reggie Dawson The 5 Most Popular Front-end Frameworks Compared by Ivaylo Gerchev The CSS Grid Layout vs CSS Frameworks Debate by Maria Antonietta Perna This book is for all frontend developers who want to build responsive, mobile-first websites. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.
Online resource; title from PDF title page (EBSCO, viewed August 9, 2018)
Keywords: Web sites -- Design; Application software -- Development; Ruby (Computer program language); Sites Web; Conception; Logiciels d'application; Développement; Ruby (Langage de programmation); COMPUTERS; Data Processing; Application software; Development; Web sites; Design